Acessibilidade e mobilidade em um residencial para idosos do município de Araraquara – SP - Teixeira, Juliana Bertin (2016)
As the aging of the population becomes a reality, it is necessary to rethink the cities to offer accessibility to all its individuals, having or not some restriction of mobility themselves. Accessibility must transcend the interior of buildings and permeate all its surroundings and the urban environment. Make the city accessible is a challenge, and this becomes even bigger when the focus is the elderly population. It must be changed the way of thinking cities, as the range of the population over 60’s that live alone is increasing, and ensuring them accessibility and mobility is a duty of the government. This study is meant to examine the accessibility and mobility of residents of a housing project for the elderly in the city of Araraquara, SP, using as reference the Brazilian Standard NBR 9050, 2015. This analysis includes the views of residents and the responsible administrative agent on the issue, as well as the use of technical parameters of ISO 9050, for the elaboration of a check list to ascertain whether the place has the necessary accessibility for this vulnerable group. The methodology consists in applying the tools MMSE test-Mini Mental State Examination, conversation circles, as well as relevant parameters of the standard NBR 9050. Initially the results pointed to a very positive perception by the elderly, although some accessibility parameters have not been included in the construction of houses and residential facilities. Furthermore, it was found very low mobility of older people when they need to perform their daily tasks, making possible by the use of transport modes on foot and by public transport by bus. Improve accessibility both internally and in mobility for the surrounding of the residence location, would be some of the possible solutions to increase security and ensure autonomy, fostered by increased mobility.